Upaya Meningkatkan Partisipasi Aktif dan Hasil Belajar Sejarah pada Materi Perang Dunia II melalui Strategi Permainan Edukatif ‘Lompat Sejarah’ - Dynika, Irfani Robbeth (Jurnal Penelitian dan Pendidikan IPS, 2025)
This study aims to increase students' active participation and learning outcomes in History subjects, especially World War II material, through the application of the “Jump History” educational game strategy. This study used a Classroom Action Research (PTK) approach with the Kemmis and McTaggart model consisting of two cycles. The research subjects were grade XI students at MAN Sumenep totaling 34 people. The instruments used include student activity observation sheets, learning outcomes tests, and documentation. The results showed a significant increase in students' active participation characterized by increased activeness in group discussions, answering questions, and involvement in the learning process. In addition, student learning outcomes also improved from pre-action to the second cycle. The application of the educational game “Jump History” proved to be able to create a fun learning atmosphere, increase motivation, and help students understand historical material more contextually. Thus, this strategy can be used as an alternative in the history learning process in the classroom.